SPECIFICS OF MATHEMATICS EDUCATION FUTURE ENGINEERS NUCLEAR INDUSTRY - Georgy M. Il’mushkin; Minevali M. Minshin (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The work is devoted to study the specifics of the mathematical education of future engineers of the nuclear industry. Determined the basic tasks of mathematical preparation of students, identified the main principles of its organization. The allocation system is the backbone of the principles and the fundamental principle of professional orientation. Expediency gradual forms of organization of mathematical preparation of students, highlighting the initial stage and revealed its essential characteristics. This mathematical education are systemically-yuschee start in the professional development of students, providing a significant impact on the quality of Prep-reparation graduates. The paper also reveals the problem of formation of mathematical competence due to the specifics of the process and content of education. Watched feasibility of personality-oriented approach to teaching mathematical disciplines, providing extensive use of modular technology alignment by means of individualized and differentiated instruction, as well as collective forms of learning technologies. The basis of the training activities on the principle of a combination of individual and collective forms of learning.